Perkembangan Istilah Literatur Hadis Nusantara Kontemporer - Majid, Abdul; Anshori, Muhammad (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2022)
This paper will expalains or discusses on the development of literature terms in Hadith sudies that developed in the Nusantara (archipelago) in modern-contemporary era. The important question that will be explained in this paper is what are the terms of Hadith literature that developed in the Nusantara in the contemporary era? The study of Hadith literature that developed in the Nusantara began to appear after Maḥfūẓ al-Tarmasī (w. 1338 H/1919 AD) wrote several works/book related to the science of Hadith. In the early period of its appearance, the study of Hadith in the Nusantara was very little, so it was rare to find Hadith book. Until the end of the 1990s, the study of Hadith was still scanty because there were little muslim scholar gave appreation to it. In the early 2000, Hadith studies began to be researched in various terms appeared in the Hadith literature. All of the terms are the big contribution from contemporary scholars of Hadith Nusantara, that will to be developed to the next period in the future.